Analisis Kepatuhan Minum Obat Anti Hipertensi pada Lanjut Usia dengan Hipertensi di Wilayah Wilayah Kerja Puskesmas Nanjungan Kabupaten Empat Lawang - Dian Marissa, Septi; Zaman, Chairil; Wahyudi, Arie (Avicenna: Jurnal Ilmiah, 2025)
Background: Blood pressure above 140 mmHg and 90 mmHg diastolic on two measurements within five minutes in a state of sufficient rest or calm is known as hypertension. This study aims to determine the analysis of compliance in taking antihypertensive drugs in the elderly in the Nanjungan Health Center Work Area, Empat Lawang Regency in 2025. Methods: The design of this study used Cross Sectional, where the population in this study was 4,745 respondents, with a sample of 369 elderly respondents aged >60 years. The sampling method in the study was purposive sampling. This study was conducted on April 22 to June 1, 2025. Data collection and retrieval using a questionnaire. Results: The results of statistical test analysis using Chi-Square statistical test and logistic regression where the results showed a significant relationship (p value <0.05) for the variables of gender (p value 0.00), education (p value 0.00), knowledge (p value 0.00), attitude (p value 0.00), side effects (p value 0.00), access to health services (p value 0.01), support from officers (p value 0.03), and family support (p value 0.00). From the results of the multivariate statistical test, the dominant factor in adherence to taking antihypertensive drugs was family support (p = 0.00; OR = 525.270). Conclusion: It is expected that health workers will pay attention to the achievement of compliance in taking antihypertensive drugs and provide counseling or education for the elderly regarding the benefits of compliance in taking antihypertensive drugs in the elderly so that it is expected to increase the target of achieving compliance in taking drugs. Keywords: Compliance, Elderly, Medication, Health Center